Diagnóstico de influência para modelos de regressão linear censurada com misturas de escala assimétrica de distribuições normais - Fuentes Guzman, Daniel Camilo (2024)
In this research, we conducted studies on local and global influence diagnostics for \sigla{SSMN-CR}{Censored Linear Regression Models with Skew Scale Mixtures of Normal Distributions}, proposed by \citeonline{guzman2020}. Initially, we discussed methods for generating censored data, specifically presenting methods to generate randomly censored data with both unilateral and interval censoring. Subsequently, we addressed case deletion and local influence diagnostics based on the Q function, inspired by the findings of \citeonline{zhu} and \citeonline{zhuelee}. To analyze the sensitivity of the maximum likelihood estimators of the SSMN-CR model parameters to small perturbations in assumptions and/or data, we considered various perturbation schemes, such as case weighting, explanatory variables, response variables, and perturbations in scale and skewness parameters. To illustrate the usefulness of the proposed methodology, we presented the analysis of a real dataset and three simulation studies.